The Influence of Job Training and Career Development on Employee Performance - Riva Ariyanti; Hardin; Fitri Rahmawati (www.amertainstitute.com, 2025)
Human capital represents a critical component within any organization or enterprise, as the achievement of organizational goals is significantly shaped by the competence and capabilities of its workforce. Given this central role, the administration of RSUD R.A.A Tjokronegoro Purworejo must give serious consideration to the performance of its personnel to ensure that institutional objectives are effectively realized. Employee performance can be shaped by multiple elements, notably including training initiatives and career progression opportunities. This research investigates the impact of professional training and career advancement on the job performance of non-medical staff at RSUD R.A.A Tjokronegoro Purworejo. Employing a quantitative methodology, data were gathered through questionnaires distributed to 84 civil servant employees. The results of regression analysis indicated that both training and career development exert a significant and positive influence on staff performance. These findings underscore the critical need to enhance training schemes and structured career development to optimize employee outcomes.